2022
DOI: 10.1097/mcg.0000000000001782
|View full text |Cite
|
Sign up to set email alerts
|

Medical Cannabis Use Patterns and Adverse Effects in Inflammatory Bowel Disease

Abstract: Goals: To investigate medical cannabis (MC) use patterns and adverse effects in patients with inflammatory bowel disease (IBD). Background: MC is now legal in many states. Although previous studies suggest improvement in disease activity among IBD patients using MC, use patterns and adverse effects are unclear. Study: A cross-sectional anonymous survey was conducted (October 23, 2020 to January 24, 2021) amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Inflammatory bowel disease (IBD), which includes Crohn's disease (CD) and ulcerative colitis (UC), is a chronic and relapsing inflammatory disorder of the gastrointestinal tract 1,2 . The global incidence of inflammatory bowel disease (IBD) increased by 47.45%, from an estimated 3.32 million cases to 4.90 million cases between 1990 and 2019, which poses significant impacts in patients' quality of life and challenges in terms of diagnosis, treatment, and management [3][4][5][6][7] . One of the key complications of IBD is the development of fibrosis, a pathological process characterized by excessive accumulation of extracellular matrix components in the affected intestinal wall 8 .…”
mentioning
confidence: 99%
“…Inflammatory bowel disease (IBD), which includes Crohn's disease (CD) and ulcerative colitis (UC), is a chronic and relapsing inflammatory disorder of the gastrointestinal tract 1,2 . The global incidence of inflammatory bowel disease (IBD) increased by 47.45%, from an estimated 3.32 million cases to 4.90 million cases between 1990 and 2019, which poses significant impacts in patients' quality of life and challenges in terms of diagnosis, treatment, and management [3][4][5][6][7] . One of the key complications of IBD is the development of fibrosis, a pathological process characterized by excessive accumulation of extracellular matrix components in the affected intestinal wall 8 .…”
mentioning
confidence: 99%
“…Although the data do not support using cannabis for altering the disease process, there have been studies with affirmative results that cannabis can alleviate symptoms of inflammatory bowel disease. A multisite cross-sectional survey found that patients with IBD who use medical cannabis find symptom improvement and decreased emergency room visits; specifically, the number of respondents reporting an emergency room visit at least once every 6 months was significantly lower after versus before medical cannabis use, as well as a statistically significant number of respondents reporting a moderate-to-major impact on their life from abdominal pain and nausea was 85.6 versus 31.8% and 53.8 versus 21.6% ( P < 0.01) [18 ▪ ]. In another survey-based study in the UK, whose study population included 76 patients with CD and 25 patients with UC, patients were prescribed cannabis-based medicinal products, and completed the following questionnaires at 1 and 3 months: Short Inflammatory Bowel Disease Questionnaire (SIBDQ), General Anxiety Disorder 7 (GAD-7), Single-Item Sleep Quality Scale (SQS) and Patient Global Impression of Change (PGIC).…”
Section: Case Studiesmentioning
confidence: 94%
“…Depending on the severity of the flares and the response to medication, IBD therapy includes anti-inflammatory agents, such as amino-salicylic acid (5-ASA), corticosteroids, immunosuppressants, biologic agents and advanced small molecules, such as Janus kinase inhibitors and sphingosine-1-phoshpate receptor modulators [ 8 ]. Despite multiple and novel therapeutic interventions, IBD treatment is still of limited efficacy and often accompanied by side effects, leading patients to seek alternative forms of treatment, such as medical cannabis (MC) [ 9 ]. In recent years, there is an increasing interest among patients and physicians, in the potential therapeutic role of MC for the treatment of IBD [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there is an increasing interest among patients and physicians, in the potential therapeutic role of MC for the treatment of IBD [10][11][12]. There are over 500 potentially active compounds within cannabis, with the two best studied compounds being cannabidiol (CBD) and ∆ 9 -tetrahydrocannibinol (THC) [13,14]. It is postulated that phyto-cannabinoids modulate inflammation via the endocannabinoid system, with CBD and THC interacting with endocannabinoid receptors in the brain, enteric nervous system, gastrointestinal epithelial cells, and both macrophages and plasma cells [15][16][17].…”
Section: Introductionmentioning
confidence: 99%